BUILDING IDENTITY IN GLOBAL REALITY: A POSTCOLONIAL STUDY ON RAJAA ALSANEA'S BANAT AR-RIYADH - Hindun Ichsan (POETIKA, 2021)
This study aims to examine the novel Banaat ar-Riyadh (Girls of Riyadh) from the perspective of globalization using a postcolonial approach. This novel was written by Rajaa Alsanea, a Riyadhi girl who moved to the United States of America and then published her novel in Lebanon. The novel was written in the form of a series of electronic mails sent by four young Riyadhi girls who discuss the contestation between traditional Saudi Arabian norms and American norms.  Fittingly, this study uses postcolonial theory, with the theoretical framework of globalization as a basis for investigating the aspects identified in the theory, such as mimicry, inferiority, and hybridity, and applies deductive qualitative method from a globalization perspective. The results of this study indicate the influence of American culture on the lives of Saudi Arabians. The influence of American culture is obtained through Saudi people, both men and women, who study and work in the United States. It is the relationship between Arab culture and American culture that influences the Arab way of thinking, which leads to certain behavioral changes. Some Arabs, previously compliant to their traditional values, display behavorial changes that are inspired by Americans, especially American women. Arab women who are supposed to constantly obey state rules, want changes which they adopt from American culture. Penelitian ini bertujuan meneliti novel Banaat ar-Riyadh dari perspektif globalisasi dengan mengambil pendekatan poskolonial. Novel ini ditulis oleh Rajaa Alsanea, seorang gadis Riyadh yang pindah ke Amerika Serikat lalu menerbitkan novelnya di Lebanon. Novel ini berbentuk rangkaian surat elektronik yang dikirimkan oleh empat sekawan gadis-gadis Riyadh yang membicarakan kontestasi antara norma-norma tradisional Arab Saudi dengan norma-norma Amerika Serikat. Oleh karena itu, penelitian ini menggunakan teori poskolonial, serta globalisasi  sebagai landasan untuk melihat aspek-aspek yang dikemukakan dalam teori tersebut, yaitu mimikri, inferioritas, dan hibriditas, dengan metode deduktif kualitatif yang ditempatkan dalam perspektif globalisasi. Hasil dari penelitian ini menunjukkan adanya pengaruh budaya Amerika pada tata kehidupan sebagian orang Arab Saudi. Pengaruh budaya Amerika itu diperoleh melalui orang-orang Arab Saudi, baik laki-laki maupun perempuan, yang menempuh studi dan bekerja di Amerika. Keterhubungan antara budaya Arab dengan budaya Amerika inilah yang memengaruhi pemikiran orang Arab, yang kemudian berdampak pada perubahan perilaku. Orang Arab yang semula berpegang teguh pada aturan-aturan tradisi kemudian menginginkan perubahan-perubahan yang mengarah pada pada perilaku orang Amerika yang mereka lihat, terutama pada perempuan. Perempuan Arab, yang diharuskan patuh pada aturan-aturan yang dibuat oleh negara, menginginkan perubahan-perubahan dengan mengadopsi budaya Amerika.